Serotonin 3A receptor subtype as an early and protracted marker of cortical interneuron subpopulations - Vucurovic, Ksenija; Gallopin, Thierry; Ferezou, Isabelle; Rancillac, Armelle; Chameau, Pascal; van Hooft, Johannes A.; Geoffroy, Hélène; Monyer, Hannah; Rossier, Jean; Vitalis, Tania (Cerebral cortex, 2010)
To identify neocortical neurons expressing the type 3 serotonergic receptor, here we used transgenic mice expressing the enhanced green fluorescent protein (GFP) under the control of the 5-HT3A promoter (5-HT3A:GFP mice). By means of whole-cell patch-clamp recordings, biocytin labeling, and single-cell reversed-transcriptase polymerase chain reaction on acute brain slices of 5-HT3A:GFP mice, we identified 2 populations of 5-HT3A-expressing interneurons within the somatosensory cortex. The first population was characterized by the frequent expression of the vasoactive intestinal peptide and a typical bipolar/bitufted morphology, whereas the second population expressed predominantly the neuropeptide Y and exhibited more complex dendritic arborizations. Most interneurons of this second group appeared very similar to neurogliaform cells according to their electrophysiological, molecular, and morphological properties. The combination of 5-bromo-2-deoxyuridine injections with 5-HT3A mRNA detection showed that cortical 5-HT3A interneurons are generated around embryonic day 14.5. Although at this stage the 5-HT3A receptor subunit is expressed in both the caudal ganglionic eminence and the entopeduncular area, homochronic in utero grafts experiments revealed that cortical 5-HT3A interneurons are mainly generated in the caudal ganglionic eminence. This protracted expression of the 5-HT3A subunit allowed us to study specific cortical interneuron populations from their birth to their final functional phenotype.
Gesehen am 19.09.2023